Atypical Emotional Electrodermal Activity in Toddlers with Autism Spectrum Disorder. Issue 9 (8th September 2020) - Vernetti, Angelina; Shic, Frederick; Boccanfuso, Laura; Macari, Suzanne; Kane‐Grade, Finola; Milgramm, Anna; Hilton, Emily; Heymann, Perrine; Goodwin, Matthew S; Chawarska, Katarzyna
Abstract : Past studies in autism spectrum disorder (ASD) indicate atypical peripheral physiological arousal. However, the conditions under which these atypicalities arise and their link with behavioral emotional expressions and core ASD symptoms remain uncertain. Given the importance of physiological arousal in affective, learning, and cognitive processes, the current study examined changes in skin conductance level (ΔSCL) in 41 toddlers with ASD (mean age: 22.7 months, SD: 2.9) and 32 age‐matched toddlers with typical development (TD) (mean age: 21.6 months, SD: 3.6) in response to probes designed to induce anger, joy, and fear emotions. The magnitude of ΔSCL was comparable during anger ( P = 0.206, d = 0.30) and joy ( P = 0.996, d = 0.01) conditions, but significantly lower during the fear condition ( P = 0.001, d = 0.83) in toddlers with ASD compared to TD peers. In the combined samples, ΔSCL positively correlated with intensity of behavioral emotional expressivity during the anger ( r [71] = 0.36, P = 0.002) and fear ( r [68] = 0.32, P = 0.007) conditions, but not in the joy ( r [69] = −0.15, P = 0.226) condition. Finally, ΔSCL did not associate with autism symptom severity in any emotion‐eliciting condition in the ASD group. Toddlers with ASD displayed attenuated ΔSCL to situations aimed at eliciting fear, which may forecast the emergence of highly prevalent internalizing and externalizing problems in this population. The study putatively identifies ΔSCL as a dimension not associated with severity of autism but with behavioral responses in negatively emotionally challenging events and provides support for the feasibility, validity, and incipient utility of examining ΔSCL in response to emotional challenges in very young children. Lay Summary: Physiological arousal was measured in toddlers with autism exposed to frustrating, pleasant, and threatening tasks. Compared to typically developing peers, toddlers with autism showed comparable arousal responses to frustrating and pleasant events, but lower responses to threatening events. Importantly, physiological arousal and behavioral expressions were aligned during frustrating and threatening events, inviting exploration of physiological arousal to measure responses to emotional challenges. Furthermore, this study advances the understanding of precursors to emotional and behavioral problems common in older children with autism. Autism Res 2020, 13: 1476–1488 . © 2020 International Society for Autism Research, Wiley Periodicals, Inc.